Work-related experiences of people who hear voices: An occupational perspective. (December 2017) - Craig, Lisa; Cameron, Josh; Longden, Eleanor
Introduction: Hearing distressing voices can be a significant mental health challenge, potentially disrupting working lives. Yet few studies have explored voice-hearing in relation to employment. This study aimed to understand the work-related experiences of voice-hearers, including the impacts on their working lives and their corresponding self-management strategies. Method: A phenomenological approach gathered data from the electronic diaries of five voice-hearers with experience of working. Data were analysed using thematic analysis. Findings: Critical and distressing voices that demanded full attention were most disruptive of people's working lives, particularly affecting concentration, communication and task completion. At times voices were experienced as neutral and, for some, as supportive of work. Meaningful experiences of work could diminish the negative impact of voice-hearing. A range of resilience strategies were used to manage voices, notably attempts to interact with voices and using activities (including work) to engage or distract them. The diary method of writing about one's experiences emerged as an unanticipated positive occupational coping strategy. Conclusion: Practitioners should pay close attention to the diversity of individual voice-hearing experiences and self-management strategies (including occupational ones) and draw on these to support their clients' participation in work.